Level of knowledge about non-ionizing radiation and use of the cell phone in university students - ZAMORA ROMERO, Pedro (2020)
The present study was carried out, with the purpose to determine the level of knowledge about non-ionizing radiation and cell phone use in students of the 1st, 2nd cycle of obstetrics at UDCH, November 2019. A study was conducted correlational, prospective cross where the following variables are considered: level of knowledge about non-ionizing radiation and the use of cell phones directly or indirectly at the time of the study. The studied sample was chosen at random, fulfilling the inclusion and exclusion criteria, where a total of 110 students are found. The level of knowledge was measured through a structured and validated survey by the researchers. It was found that the level of knowledge about non-ionizing radiation was 58.4%, being of a low level of knowledge, regarding the use of cell phones, 69.4% used the cell phone in an inappropriate way, 59.3% of the female students have low knowledge of non-ionizing cell phone radiation, 66.7% of male students have medium knowledge of non-ionizing cell phone radiation. Where it was determined that there is a relationship between the low level of knowledge about non-ionizing radiation and the use of cell phones.Keywords: non-ionizing radiation, cell phone, telecommunication, electromagnetic radiation, knowledge.